Research in Education Draws Widely From the Social Sciences and Humanities - Lund, Kristine; Jeong, Heisawn; Grauwin, Sebastian; Jensen, Pablo (Frontiers in Education, 2020)
It is well known that education related research is carried out within different disciplines and frameworks, but how is it specifically connected through citations to the larger social sciences and humanities? And how can this knowledge be mobilized to improve dialogue between researchers in different communities, given the benefits of integrating different frameworks and methods? We used different scientometric methods to show where exactly research in education connects to social sciences and humanities. This multidisciplinary context provokes a set of integration challenges for research in education. We propose how our work can supplement an existing model in order to give a framework for meeting these challenges with the goal of achieving broader education-related collective knowledge advancement.